2011
DOI: 10.1071/zo10083
|View full text |Cite
|
Sign up to set email alerts
|

Haemorheology of the eastern grey kangaroo and the Tasmanian devil

Abstract: The blood of two Australian marsupials, the eastern grey kangaroo (Macropus giganteus) and the Tasmanian devil (Sarcophilus harrisii), has been reported to have greater oxygen-carrying capacity (i.e. haemoglobin content) when compared with that of placental mammals. We investigated whether alterations of blood rheological properties are associated with the increased oxygen-carrying capacity of these marsupials. Eastern grey kangaroos (n = 6) and Tasmanian devils (n = 4) were anaesthetised for blood sampling; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…It was found that HVR for healthy women (CON) were comparable to earlier reports [18, 19], and women with PCOS presented with significantly decreased HVR at all shear rates (main effect p < 0.001). At the highest measured shear rates (750 and 1500 s -1 ), HVR was 8% lower in PCOS; the reduction became greater at 300 (10%), 150 (11%) and 75 s -1 (12%).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…It was found that HVR for healthy women (CON) were comparable to earlier reports [18, 19], and women with PCOS presented with significantly decreased HVR at all shear rates (main effect p < 0.001). At the highest measured shear rates (750 and 1500 s -1 ), HVR was 8% lower in PCOS; the reduction became greater at 300 (10%), 150 (11%) and 75 s -1 (12%).…”
Section: Resultssupporting
confidence: 83%
“…Haematocrit-to-viscosity ratio (HVR) was calculated for whole blood at native haematocrit by expressing haematocrit (%) to blood viscosity at each shear rate. The HVR has been explored as an index of oxygen delivery effectiveness of RBC based on the rationale that increased numbers of RBC is concurrently beneficial for oxygen transport, but also negatively increases blood viscosity, and therefore resistance to flow [18, 19]. …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown the viscosity of WB, which is known to increase with aging, to vary between 5 and 120 mPa. 47 Using a chip resembling the microfluidic structure of the final cartridge, the coagulation risk of heparinized WB with various dilution factors was evaluated after a 30 min incubation period. Results revealed no clotting incidence in the 1 : 4 diluted heparinized WB samples as well as negligible effects on the LoD and LoQ of the OsteoLab using these samples.…”
Section: Resultsmentioning
confidence: 99%
“…Blood can carry the necessary nutrients to tissues and organs as long as it continues its normal flow pattern in the circulatory system. This normal flow is particularly important in the pulmonary vascular bed in order that gas exchange can be performed optimally [1417]. Vessel constitution and the fluidity of blood need to be normal for normal blood flow [18, 19].…”
Section: Discussionmentioning
confidence: 99%